Multimodalitas Representasi Laki-Laki pada Iklan Skincare di Media Sosial Instagram Somethinc - Tafrijiyah, Kaamilah; Rahmaida, Hana Fauzia (Faculty of Da'wa and Communications Sciences, 2025)
This study aims to analyze the representation of men in the campaign poster of the beauty product